2017
DOI: 10.1002/14651858.cd011967.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral anti-diabetic pharmacological therapies for the treatment of women with gestational diabetes

Abstract: There were insufficient data comparing oral anti-diabetic pharmacological therapies with placebo/standard care (lifestyle advice) to inform clinical practice. There was insufficient high-quality evidence to be able to draw any meaningful conclusions as to the benefits of one oral anti-diabetic pharmacological therapy over another due to limited reporting of data for the primary and secondary outcomes in this review. Short- and long-term clinical outcomes for this review were inadequately reported or not report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 94 publications
0
44
0
Order By: Relevance
“…Preterm birth was increased in women who were treated with metformin. In contrast, a recent systematic review compared outcomes between women randomized to either glyburide or metformin from several additional studies and found no differences in maternal or neonatal outcomes 86. The authors noted that most of the studies comparing glyburide with metformin were of moderate to low quality, and they also stressed that the benefits and potential harms of one oral antidiabetic drug therapy compared with another are unclear.…”
Section: Glyburide Versus Metforminmentioning
confidence: 97%
“…Preterm birth was increased in women who were treated with metformin. In contrast, a recent systematic review compared outcomes between women randomized to either glyburide or metformin from several additional studies and found no differences in maternal or neonatal outcomes 86. The authors noted that most of the studies comparing glyburide with metformin were of moderate to low quality, and they also stressed that the benefits and potential harms of one oral antidiabetic drug therapy compared with another are unclear.…”
Section: Glyburide Versus Metforminmentioning
confidence: 97%
“…The evidence for the real‐world comparative effectiveness of metformin versus insulin, however, is limited and inconclusive. The most recent Cochrane review of oral antidiabetic agents for treating GDM could not recommend nor refute use of metformin for this purpose on the basis of available evidence …”
Section: Introductionmentioning
confidence: 99%
“…The current standard of care is to optimize maternal blood sugar levels before and during pregnancy [11]. While this has certainly decreased some perinatal morbidities, infants born to mothers with good glycemic control continue to have a higher risk of heart disease [12][13][14][15] and gestational diabetes can predispose infants to macrosomia and programmed cardiometabolic disease as adults, even if their mother was treated during pregnancy [16][17][18][19][20][21][22][23][24]. This suggests there are additional under-recognized, targetable risk factors including lipids.…”
Section: Introductionmentioning
confidence: 99%